Regional Competitiveness and Its Implications for Development - Soebagyo, Daryono; Triyono, Triyono; Cahyono, Yuli Tri (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
This study was conducted to identify regional competitiveness in some areas of Central Java. Regional competitiveness became one of the issues in regional development policy since the enactment of local autonomy.Measurement of regional competitiveness has been mostly done through ranking as a benchmark the competitiveness of the region. Mapping regional competitiveness in Indonesia has been made to all counties and cities, which shows the competitiveness ranking of each region. Competitiveness ranking is based on the characteristics of the area assessed the competitiveness of the input and output competitiveness. Even though the mapping of regional competitiveness in Central Java in particular has never been done, but the result of the national and regional competitiveness can be used as a reference to determine the ranking of each district / town in Central Java. Distribution competitiveness ranking the 15 districts / cities in Central Java can be grouped based on input competitiveness and the competitiveness of output.